Roman legal basis for the protection of the lease agreement parties - PRYMAK, Володимир (Ius Modernum, 2024)
The reception of Roman law is determined by the proven effectiveness of the legal tools developed and implemented in practice in ancient Rome. The problem of ensuring the effectiveness of legal regulation in the interaction of adjacent models of regulatory and protective legal relations with the participation of the parties to the lease contract remains relevant even today, especially in the conditions of martial law. In view of the outlined problem, the purpose of the article is to determine the classification criteria for building a system of forms and ways of protection of the rights and interests of the parties to the lease contract, originally determined by the development of Roman law, which will contribute to the application of proper and effective ways of protecting the rights and interests (remedies) of lessors and lessees. Implementation of the goal was ensured mainly by systemic, formal-legal and structural-functional methods, as well as induction and deduction methods. The system method, for example, contributed to the determination of the relationship between regulatory and protective legal relations in ensuring the implementation of the functions and principles of objective civil law within the framework of employment legal relations. In the course of the study, it was established that the systematization of the forms and ways of protection of the rights and interests (remedies) of the parties to the lease contract involves the need to distinguish the grounds for the use of jurisdictional (judicial and notary) or non-jurisdictional (in the form of self-defense) mechanisms for the use of legal means aimed at: determining the dynamics of legal relations within lease contract due to change or termination of the obligation, in particular as a result of unilateral refusal of the contract; forced fulfillment in kind of the obligation to transfer (return) the subject of the lease agreement or to pay payments for the use of the thing; the application of measures of civil liability in the form of a penalty, three percent of annual and inflationary losses, compensation for damages, and in cases stipulated by the contract – and moral damage. The results of the research made it possible to formulate a number of theoretically and practically significant conclusions. In particular, it is emphasized that the Roman legal basis of the civil protection of the parties to the contract of lease consists in the objective determination of a whole system of ways of protecting the subjective rights and interests of the lessor and the lessee by the characteristics of an individually defined non-consumable thing as the subject of the corresponding contract, and this deed – as a consensual, bilateral, paid, defined in term of time transaction (in the sense of temporary use of someone elseʼs property), the relations of the parties are based on the principles of justice, reasonableness and good faith.